Multiple novel gene-by-environment interactions modify the effect of FTO variants on body mass index. - Young, A; Wauthier, F; Donnelly, P (Nature Publishing Group, 2016)
Genetic studies have shown that obesity risk is heritable and that, of the many common variants now associated with body mass index, those in an intron of the fat mass and obesity-associated (FTO) gene have the largest effect. The size of the UK Biobank, and its joint measurement of genetic, anthropometric and lifestyle variables, offers an unprecedented opportunity to assess gene-by-environment interactions in a way that accounts for the dependence between different factors. We jointly examine the evidence for interactions between FTO (rs1421085) and various lifestyle and environmental factors. We report interactions between the FTO variant and each of: frequency of alcohol consumption (P=3.0 × 10(-4)); deviations from mean sleep duration (P=8.0 × 10(-4)); overall diet (P=5.0 × 10(-6)), including added salt (P=1.2 × 10(-3)); and physical activity (P=3.1 × 10(-4)).